Reading novels - Hughes, George, 1944- (Vanderbilt University, 2002)
A piece of practical criticism, this text is a comprehensive "poetics" of a genre that has not attracted a great deal of attention. It is a reader's and student's guide that reaches beyond issues of individual texts and historical traditions to essentialfeatures of the form of the novel.